WHEN YOU HEAR HOOVES THINK PERCHERON HORSES NOT ZEBRAS. Issue 10 (9th September 2014) - Dharia, Sonali; Sittampalam, Mara; Shah, Alexander; Jones, Jonathan; Nor, Azli Mohd; Edwards, Simon
Abstract : Stroke is a medical emergency, requiring prompt assessment for those presenting within 3 to 4.5 hours. However certain presentations cause diagnostic uncertainty, rendering patients unthrombolysable due to an alternate diagnosis being made. We present two patients with decreased level of consciousness as a result of a stroke. Patient 1: a 73 year old male who presented with a sudden collapse. His GCS was 6 on arrival without any history of seizure. It was unclear whether a cardiac or respiratory arrest caused his collapse. Neurological examination revealed sluggish pupils with miosis on the left and loss of the oculo-cephalic reflex. He could move his limbs spontaneously, with localisation to painful stimuli. Patient 2: a 49 year old female Who presented acutely with drowsiness but no localising signs. She improved slightly by day 4, and referred to Neurology when examination of eye movements revealed convergence spasm and restriction of abduction and upgaze bilaterally. MRI in both cases revealed bithalamic infarcts, highly suggestive of an Artery of Percheron occlusion. We will review published Artery of Percheron presentations and our patients in order to highlight the need for a high index of suspicion when managing acute neurological presentations of brainstem strokes.